Paravertebral Muscle Mechanical Properties and Spinal Range of Motion in Patients with Acute Neck or Low Back Pain: A Case-Control Study - Sandra Alcaraz-Clariana; Lourdes García-Luque; Juan Luis Garrido-Castro; César Fernández-de-las-Peñas; Cristina Carmona-Pérez; Daiana Priscila Rodrigues-de-Souza; Francisco Alburquerque-Sendín (Diagnostics, 2021)
Our aims were to identify potential differences in muscle mechanical properties (MMPs) of cervical and lumbar tissues and in spinal range of motion (ROM) between patients with acute low back pain (LBP) or acute neck pain (NP) and healthy controls, and to identify if ROMs and MMPs are able to identify subjects among the three groups. Clinical variables (pain, disability, fear of movement, kinesiophobia, quality of life), MMPs and ROMs were obtained in 33 subjects with acute LBP, 33 with acute NP, and 33 healthy control subjects. Between-groups differences and explanatory models to discriminate groups depending on MMPs and ROMs were calculated. The results showed that cervical tone was higher in patients with acute NP than in controls, while cervical decrement was higher in both spinal pain groups. Patients with acute NP showed reduced cervical flexion when compared to acute LBP and control groups, and also cervical rotation, but just against controls. Furthermore, lumbar flexion was reduced in patients with acute LBP when compared to those with acute NP. Cervical decrement was able to discriminate spinal pain individuals from controls in a multinominal regression (R2: Cox–Snell estimation = 0.533; Nagelkerke estimation = 0.600). Lumbar flexion differentiated patients with acute LBP and controls, whereas cervical flexion differentiated patients with acute NP and controls. This study supports a tendency of the affectation of other spinal regions when only one is affected.